Statistical and Perceived Diversity and Their Impacts on Neighborhood Social Cohesion in Germany, France and the Netherlands - Ruud Koopmans; Merlin Schaeffer (Social Indicators Research, 2016)
The question whether ethnic diversity is associated with declining social cohesion has produced much controversy. We maintain that more attention must be paid to cognitive mechanisms to move the debate ahead. Using survey data from 938 localities in Germany, France, and the Netherlands, we explore a crucial individual-level mechanism: perceptions of diversity. We not only consider perceptions of the amount, but also of the qualitative nature of diversity. By asking about various qualitative aspects of diversity, we test the cognitive salience of three explanations that have been proposed in the literature for negative diversity effects: out-group biases, asymmetric preferences and coordination problems. We show that all three mechanisms matter. Perceptions both mediate statistical diversity effects, and have important explanatory power of their own. Moreover, we are able to address the question to what extend the relationship of perceived diversity and neighborhood social cohesion varies across policy contexts. Based on assumptions in the literature about positive impacts of inclusive and culturally pluralist immigrant integration policy approaches, we hypothesize that ethno-cultural diversity is less negatively related to neighborhood social cohesion in more inclusive policy contexts. Our results provide partial support for this hypothesis as perceived diversity has a significantly stronger negative impact on neighborhood cohesion in Germany.
Keywords: 300; social cohesion; social capital; ethnic diversity; immigration; intergroup relations; community erosion